SISTEM PAKAR PENDIAGNOSA PENYAKIT PADA TANAMAN KAKAO BERBASIS WEB (Information Technology and Telematics, 2014)
Abstrak - The purpose of this research is to design and build an expert system to determine the type of web-based cocoa plant diseases are based on physical characteristics and symptoms until ditemukannyua medical advice in the form of information about the disease to the cocoa crop in question. Analysis tools used in this research is to create a knowledge base which is then followed as an input in the process of debriefing on fordward method chaining using if-then rules. As well as making the display interface to allow a user to access the information. This research has resulted in disease diagnostic expert system on Web-Based Cocoa Plants that can diagnose diseases through the symptoms and then give a solution of any disease. This research is still simple that further research needs to be done to determine the plant disease symptoms in cocoa, cocoa plant diseases that others can be treated Keyword Expert System, Disease, Plant Cocoa